Київське міське товариство греків: історія і сучасність - Піскіжова, В. (Міжнародні зв’язки України: наукові пошуки і знахідки, 2017)
Статтю присвячено історії становлення та діяльності однієї із
перших в історії незалежної України громадських організацій вітчизняної
грецької спільноти — Київському міському товариству греків. Адже в
сучасному світі громадські об’єднання національних меншин є надзвичайно важливим структурним компонентом громадянського суспільства, що може відігравати як консолідуючу роль, так і слугувати джерелом загострення міжнаціональних конфліктів. Основою джерельної
бази дослідження стали матеріали Поточного архіву цієї організації
(Статут, Протоколи засідань, Постанови, Угоди та ін.), частину з яких
у 2017 р. вже було передано на збереження до фондів Центрального
державного архіву громадських об’єднань України. Однак до цього часу
ці документи ще не стали доступними для широкого загалу зацікавленої громадськості. The article is devoted to the history of the formation and activity of one of
the first in the history of independent Ukraine public organizations of the
national Greek community, i.e. the Kyiv City Association of the Greeks. After
all, in today’s world, public associations of national minorities are an extremely
important structural component of the civil society, which can play both a
consolidating role and serve as a source of aggravation of interethnic conflicts.
The grounds of the source base of the research were the materials of the
current archive of this organization (the Statute, protocols of meetings,
resolutions, agreements, etc.), part of which in 2017 was already transferred to
the funds of the Central State Archives of public associations of Ukraine.
However, up to now, these documents have not become available yet to the
general public concerned. Taking this into consideration, we find it appropriate
to publish some of them in the full volume as an annex to this research,
especially those that most clearly highlight the main achievements of the
organization in the development of national and cultural life of the Greek
community of Kyiv and Ukraine in general, and show the dynamics of the
establishment of the Ukrainian-Greek intercultural dialogue. Important
information on the activity of the Kyiv City Association of the Greeks is found
on the pages of its printed edition, the newspaper “Elpida”, as well as on the
organization site operating since 2016.
The importance of recording and systematization of information on the
current institutional development of national minorities in Ukraine is preconditioned
by the necessity to form a conscious evaluation of the role of
associations of national minorities in the process of forming public associations
and the establishment of national Ukrainian culture in opinion of
public and scientific communities.